Effects of Pandemic COVID - 19 on Basic Education: Challenges and Perspectives for the 21st Century - Aguiar, Denise Regina da Costa; Camargo-Cruz, Paulo Eduardo Alves; Resende, Flávia Grecco (Periódico Eletrônico Fórum Ambiental da Alta Paulista, 2021)
The aim of this research was to analyze studies published in 2020, related to the COVID-19 pandemic, its implications and to highlight the challenges and perspectives for rethinking Basic Education in Brazil, in the post-pandemic period. For this, the qualitative methodological approach was used, with a literature review based on scientific papers and essays published in journals indexed in the SciELO database. The analysis of the selected content was based on Bardin (2011), in order to identify in the selected papers the presence of characteristics that corroborated in the construction of this study. It was concluded that the resumption of classroom teaching in the post-pandemic period needs to be planned, evaluated, monitored and redirected continuously, carried out with great seriousness and commitment to the teaching-learning processes and the right to quality education for all children and young people, until the situation of school failure and the educational and social exclusion that exist in contemporary schools is effectively overcome, a great challenge for the 21st century.